Evolving role of immunotherapy in the treatment of refractory warts - Devinder M Thappa; Minu J Chiramel (Wolters Kluwer Medknow Publications, 2016)
Cutaneous and genital warts are common dermatological conditions caused by the human papilloma virus (HPV). Although it is a benign condition, it causes disfigurement, has a tendency to koebnerize, and can be transmitted to others. This makes adequate and timely treatment important. There are several conventional treatments available with variable response. Topical and systemic immunotherapy has now found a significant place in the treatment of warts because of its nondestructive action, ease of use, and promising results. Through this review, we would like to present a brief overview of the various immunotherapeutic agents used. These include more established agents such as imiquimod, Mycobacterium w vaccine, bacillus Calmette-Guérin vaccine, measles, mumps, and rubella vaccine, Candida antigen, trichophyton antigen, tuberculin, zinc, cimetidine, levamisole, HPV vaccine, and autoimplantation therapy. Other agents such as contact immunotherapy which is sparsely used now than before and newer agents such as Corynebacterium parvum, sinecatechins, echinacea, propolis, glycyrrizinic acid, and Vitamin D have also been discussed. The mechanism of action of these agents, along with their dosage, mode of administration, duration of use, expected outcomes and comparative efficacy, evidence for their use, and expected side effects, if any, are reviewed.